KELOMPOK USAHA PIJAT DI PANTAI KELURAHAN BENOA DALAM KONTEKS INDUSTRI PARIWISATA: SEBUAH KAJIAN BUDAYA - Triariani, Nyoman (JURNAL KEPARIWISATAAN, 2010)
The objective of this study is to analyze the phenomenon of cultural tourism, especially the local massage service association on the coast of Benoa, Badung, Bali. The social theories as the basis of the study are as follows: poststructural, motivation and gender. The research employed qualitative research design and the data were collected by interviewing some key informants: entrepreneur-; managers, government officers, tourists, and local people. The research found out that: the existence of the local massage service association played an integral part of the development system of cultural tourism and gave economic benefits to local community, the use of various focal spa products such as coconut oil, the hegemony of the association of local massage service caused by the development of Spa at the hotels in the area.